2006
DOI: 10.1111/j.1399-3054.2006.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and heterologous expression in Saccharomyces cerevisiae of a mevalonate diphosphate decarboxylase cDNA from Ginkgo biloba

Abstract: Mevalonate diphosphate decarboxylase (MVD; EC4.1.1.33) catalyses the conversion of mevalonate diphosphate to isopentenyl diphosphate (IPP), which is a key skeleton for numerous functionally important secondary metabolites. A full‐length cDNA of MVD was isolated from Ginkgo biloba (designated as GbMVD) using rapid amplification of cDNA ends (RACE). GbMVD was 1958 bp with poly(A) tailing and contained a 1290‐bp open reading frame encoding a 430‐amino acid protein. The deduced GbMVD protein had a deduced molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…GbMVD Transcript Levels by Ginkgo Organs Pang et al (2006) showed that GbMVD was expressed in the roots, stems, and leaves. We extended the analysis of the organ expression pattern of GbMVD to additional organs of ginkgo via qRT-PCR.…”
Section: Responsiveness Of the Gbmvd Promoter In Tobacco Plant Towardmentioning
confidence: 98%
See 1 more Smart Citation
“…GbMVD Transcript Levels by Ginkgo Organs Pang et al (2006) showed that GbMVD was expressed in the roots, stems, and leaves. We extended the analysis of the organ expression pattern of GbMVD to additional organs of ginkgo via qRT-PCR.…”
Section: Responsiveness Of the Gbmvd Promoter In Tobacco Plant Towardmentioning
confidence: 98%
“…Ginkgo genome walker libraries were constructed using the Genome Walker Universal Kit User (Clontech, USA). To clone the promoter region of GbMVD, two rounds of PCR were performed using gene-specific primers (GbMVDP1 and GbMVDP2) that were designed according to the sequence of GbMVD cDNA (AY757921; Pang et al, 2006) and the adapter primers (AP1 and AP2) provided in the kit. The primers are listed in Table 1.…”
Section: Construction Of Genomic Library and Isolation Of Promoter Rementioning
confidence: 99%
“…EhMDC in roots was more abundant than that in stems and leaves (Figure 4). Pang et al (2006) tested the GbMVD expression in Ginkgo biloba using RT-PCR. They found that GbMVD was transcribed in root, stem and leaf, and there was no distinct difference in their transcription levels [28].…”
Section: The Organ-specific Expression Pattern Of the Ehmdc Genementioning
confidence: 99%
“…Pang et al (2006) tested the GbMVD expression in Ginkgo biloba using RT-PCR. They found that GbMVD was transcribed in root, stem and leaf, and there was no distinct difference in their transcription levels [28]. To assess the organ-specific and environmentally responsive characteristics of GbMVD expression, Liao et al (2016) fused GbMVDpro to GUS reporter gene.…”
Section: The Organ-specific Expression Pattern Of the Ehmdc Genementioning
confidence: 99%
“…A full-length cDNA of MVD from G. biloba (GbMVD) was isolated and characterized. [23] The full-length cDNA of GbMVD was 1,958 bp with a poly (A) tailing, containing an ORF of 1,290 bp encoding 430 amino acids. There was a 5’-UTR of 291 bp upstream from the start codon with G as putative transcription start, and the coding region was followed by 3’-UTR that was 345 bp-long downstream from the stop codon.…”
Section: Ginkgolides Biosynthetic-related Enzymes and Genesmentioning
confidence: 99%